Theodor Heuss, Aufbruch im Kaiserreich - Heuss, Theodor (Briefe, 2009)
The years leading up to World War I were very influential for Theodor Heuss' development. As a school pupil in Heilbronn, a student in Munich and Berlin, and an editor in Berlin and Heilbronn, he made experiences that were to prove decisive for his later career. Besides politics he was also especially involved in the fields of visual art, literature and journalism. He continually advocated a radical departure from the German Kaiser Reich, perceiving it as authoritarian, and was farsighted in his later comments on the disaster of World War I.